Implementation of Risk Management in Malaysian Construction Industry: Case Studies. (28th July 2015) - Abdul-Rahman, Hamzah; Wang, Chen; Sheik Mohamad, Farhanim
Abstract : Construction industries are exposed to wide array of risks, such as financial, design, and contractual ones, which might have a direct impact on their performance toward achieving the desired objectives. Risk Management is a proactive decision-making process used to minimize and manage the risks in the most efficient and appropriate manner. However, most construction firms in Malaysia do not apply formal risk management in their projects. Thus, this study aims to identify the actual process of risk management that is being applied in the construction projects and to determine the effects of risk management implementation on the performance of the construction projects in terms of time and cost. The data were obtained from four case studies in Kuala Lumpur, Malaysia, through semistructured interviews. It was found that the implementation of risk management process in Malaysian construction industry is still at a low level, mainly due to the fact that most of the construction employees involved in risk management are not fully aware of the available risk management techniques that can be applied in construction projects.